Media Pembelajaran Praktikum Jaringan Komputer Berbasis Augmented Reality dengan Metode Marker Based Tracking - Wulandari, Suci; Dafitri, Haida; Lubis, Yessi Fitri Annisah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to create a learning media for computer network practicum based on Virtual Lab simulation using Augmented Reality (AR) technology that can be used by Istiqlal Vocational High School students to direct computer networks anytime and anywhere. This learning media is created to help students understand the basic concepts of 3D object computer networks that appear in the real world through mobile devices in a more interactive and interesting way. The method used in this study is Marker Based Tracking. This learning media utilizes markers to display 3D learning objects that can be interacted with by students, thus helping them understand the material more deeply and practically. The results of the study showed that the use of AR with the Marker Based Tracking method was effective in improving students' understanding of computer network material. Students were more interested and active in practicums, and were able to apply theories in real 3D object simulations, which increased the effectiveness of learning. Based on the results of trials on 23 respondents, most users gave positive responses to the 3D objects provided, with 91.7% of users assessing the 3D objects presented as good quality, and 75% felt that this application increased interest in learning. In addition, 83.3% of respondents felt helped in understanding the material.